Factors associated with health and oral health-related quality of life of children and adolescents with cerebral palsy - Rodrigues Cardoso, Andreia Medeiros; Davino de Medeiros, Mariana Marinho; Gomes, Lays Nobrega [UNESP]; Martins, Mariana Leonel; Nascimento Padilha, Wilton Wilney; Cavalcanti, Alessandro Leite (Wiley-Blackwell, 2018)
AimsTo verify factors associated with impact on Health-Related Quality of Life (HRQoL) and Oral Health-Related Quality of Life (OHRQoL) of children and adolescents with cerebral palsy (CP). Methods and resultsSample of 149 individuals with CP aged 2 to 18 years and their caregivers, who provided information regarding HRQoL (PedsQL 4.0), OHRQoL (PedsQL 3.0 Oral Health, and socioeconomic factors. A calibrated investigator performed dental examinations, with dental caries, traumatic dental injury, periodontal, and occlusal evaluation. HRQoL and OHRQoL scores were transformed into a 0 to 100 scale, dichotomized in absence or presence of impact (score<50) and analyzed by Mann-Whitney test and Poisson regression (=.05). The mean HRQoL score was 50.3 10.2. Impact on HRQoL was observed in 51.7% and associated with gender, general health perception, and communication skills. The mean OHRQoL score was 78.0 +/- 24.6. The presence of impact on OHRQoL (12.1%) was associated with age, presence of gastroesophageal reflux, dental caries, and periodontal diseases. ConclusionIndividuals with CP had low HRQoL and OHRQoL scores. The impact on HRQoL was shown to be associated with gender, health perception. and communication skills. Regarding OHRQoL, the presence of impact was associated with age, gastroesophageal reflux, dental caries. and periodontal diseases.
Keywords: cerebral palsy; oral health; quality of life